2002
DOI: 10.1634/stemcells.20-3-249
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Size‐Sieved Stem Cells from Human Bone Marrow

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
180
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 250 publications
(189 citation statements)
references
References 43 publications
7
180
1
1
Order By: Relevance
“…We have previously investigated the signaling pathways involved in chondrogenesis under the control of type I and type II collagen, TGF␤1, and platelet-rich plasma (3,4,32,33,38). Building on the observations from our previous studies, we established a coculture system in which MSCs were directed toward chondrogenesis under the influence of mature chondrocytes, thereby creating a better simulation of physiologic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously investigated the signaling pathways involved in chondrogenesis under the control of type I and type II collagen, TGF␤1, and platelet-rich plasma (3,4,32,33,38). Building on the observations from our previous studies, we established a coculture system in which MSCs were directed toward chondrogenesis under the influence of mature chondrocytes, thereby creating a better simulation of physiologic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously investigated the methods of purification, characterization, differentiation, and application of multipotent MSCs (10,(32)(33)(34)(35). We have also studied the expression of matrix proteins, the type I and type II collagens, which induce chondrogenesis in human MSCs under the influence of TGF␤1 (3).…”
mentioning
confidence: 99%
“…In addition, several other studies provided direct evidence that BM stem cells are heterogenous and perhaps pluripotent. [84][85][86][87] For example, BM was found to contain endothelial-, 26 bone-, 31,88 skeletal muscles- 34 and cardiac-TCSC. 38 Interestingly, those endothelial-, skeletal muscle and cardiac-TSC were found to be CXCR4 þ CD45 À .…”
Section: Heterogenous Populations Of Stem Cells In Bone Marrow M Kucimentioning
confidence: 99%
“…Such a possibility was suggested in a recently published report. 87,[108][109][110] Mankind is searching for a key to longevity and there is no doubt that stem cells could be an important answer to this problem. Thus, there is a need for a reliable source of stem cells and adult TCSC could potentially provide a real-therapeutic alternative for embryonic stem (ES) cells and therapeutic cloning.…”
Section: Therapeutic Implications For Tcscmentioning
confidence: 99%
“…However, STRO-1 antigen is progressively lost in culture (30). Additionally, in some reported studies, bone marrow-derived MSCs had negative (31) or only dimly positive (14) expression of STRO-1. With regard to MSCs derived from locations other than the bone marrow, Gronthos and colleagues reported that STRO-1 antigen was not detected in human adipose tissue-derived stromal cells in contrast to findings in human bone marrow-derived stromal cells (10), although Zuk et al reported that the rate of expression of STRO-1 was 31% in adipose tissue-derived MSCs (8).…”
mentioning
confidence: 97%